Analisis Pelatihan dan Pengembangan Sumber Daya Manusia di Solusi Tata Ruang Interior - Putra Adityana, Boby Bayu; Kustiwa, Atep (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
This research aims for in-depth analysis to find out the extent to which the effectiveness of training and development of HR at Solusi Tata Ruang (STR) Interior. such as things - what things are obstacle factors in conducting training and development of HR at Solusi Tata Ruang (STR) Interior and also how the benefits of doing this. In this study, researchers used a qualitative type of research method. By explaining in detail related to training and development in the Interior Layout Solution (STR) company. The results of this study Overall, training and development of human resources at STR Interior has had a positive impact on improving the ability and work readiness of employees, but there are still obstacles that must be improved such as systems, documentation, long-term planning , as well as active involvement from management in the continuous development process. Training provides benefits in terms of improving technical skills, work efficiency, and reducing errors in carrying out tasks, as applied in the company Solusi Tata Ruang (STR) Interior through training in design software and working drawings. Meanwhile, development focuses on building character, leadership, and readiness for greater responsibility through programs such as mentoring and job rotation.